Testing of asset and profit strategy through investment portfolio formation in Baltic States stock exchange - Cibulskienė, Diana; Brazauskas, Martynas (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The paper aims, after presenting the possibilities of investment portfolio formation according to the asset and profit strategy, to carry out the analysis of this strategy testing in the Baltic States stock market and to assess its efficiency. The research showed that acquiring the companies whose balance value, the net current asset value and the profit are relatively low, it is possible to achieve better results than the market’s. Periodically changing the investment portfolio composition and re-evaluating the companies, better results are achieved than when applying the “buy and hold” strategy. And the use of combined index allows to avoid drawbacks that are specific for individual indicators, thus improving the results of portfolio
Keywords: kształtowanie portfela inwestycyjnego; strategia majątkowa i finansowa; strategia finansowa; analiza fundamentalna; wartość inwestycyjna